Post Partum’s Knowledge about Breast Care at Niar Patumbak Clinic - Indrawati (Caring: Indonesian Journal of Nursing Science, 2020)
Woman tend to treat the breast during the puerperium (breastfeeding period) to streamline the breastfeeding process. It’s due to maximize the breast function as the only producer of breast milk, and found good for newborns. This study aims to determine the knowledge of mothers about breast care using a cross-sectional study design. The sampling method used was purposive sampling with a sample size of 41 respondents and the tools used in data collection were questionnaires. The results of this study showed that the majority of mothers with high school education with a focus on taking care of the household had a sufficient level of knowledge in carrying out breast care, around 58,5% as many as 24 mothers. It is hoped that health workers can further improve education about breast care by frequently providing information such as counseling at health centers or when implementing Posyandu and carrying out cross-sectoral cooperation to increase maternal knowledge about breast care.